THE USE OF APPROPRIATE VOCABULARY OF THE FIRST GRADE STUDENTS OF SMA NEGERI 6 KOTA BENGKULU - Novita Purnamasari; Bambang Suwarno (JOALL (Journal of Applied Linguistics and Literature), 2016)
The purpose of this study was to evaluate the use of appropriate vocabulary by the first grade students of SMAN 6 Kota Bengkulu. Population of this research was all of the first grade students of SMAN 6 Kota Bengkulu. They were 198 students. The number of the sample was taken 25 % of the population. They were 50 students who were selected randomly. They were given a multiple choice vocabulary test with four choices. The result of this research showed that the vocabulary appropriateness by the first grade students of SMAN 6 Kota Bengkulu were as follows: deficient category was 6 %, mediocre category was 58 %, good category was 28 %, and very good category was 8 %. From the result of the study, it can be concluded that the vocabulary appropriateness by most of the first grade students of SMAN 6 Kota were in mediocre category. For further research, it is recommended to find out the factors that was faced the students in the use of appropriate vocabulary.